1998
DOI: 10.1520/jfs16085j
|View full text |Cite
|
Sign up to set email alerts
|

Cause and Manner of Death in Fatalities Involving Methamphetamine

Abstract: We reviewed a series of deaths in which methamphetamine was detected in the decedent's blood. Analysis of postmortem whole blood was performed by gas chromatography/mass spectrometry with a limit of quantitation of 0.05 mg/L. Methamphetamine was detected in 146 cases; 52 were drug caused, i.e., a death in which the direct toxic effects of the drug caused or contributed to the death, 92 were classified as drug related, i.e., a death in which the drug was demonstrated in the blood, but did not directly cause dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
83
1
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(113 citation statements)
references
References 29 publications
25
83
1
4
Order By: Relevance
“…Although the METH doses we modeled were less than the daily 0.5-1 g quantities self-reported in the human study by Simon et al, those amounts may represent overestimates since they were not independently verified for either METH quantity or drug purity. Nonetheless, the estimated peak plasma METH concentrations of 1-3 mM during the past 2 months of this experimental exposure did correspond to plasma METH concentrations measured in several studies of human abusers (Miyazaki, 1986;Logan et al, 1998;Melega et al, 2007).…”
Section: Pharmacokinetic Modelingsupporting
confidence: 76%
“…Although the METH doses we modeled were less than the daily 0.5-1 g quantities self-reported in the human study by Simon et al, those amounts may represent overestimates since they were not independently verified for either METH quantity or drug purity. Nonetheless, the estimated peak plasma METH concentrations of 1-3 mM during the past 2 months of this experimental exposure did correspond to plasma METH concentrations measured in several studies of human abusers (Miyazaki, 1986;Logan et al, 1998;Melega et al, 2007).…”
Section: Pharmacokinetic Modelingsupporting
confidence: 76%
“…Other fatalities have arisen from septic injection or asphyxia by aspiration of vomitus [57]. A number of studies suggest that a significant and possibly greater proportion of methamphetamine-related fatalities arise from accidents, suicide and homicides, suggesting severe psychological and behavioural disturbances at toxic doses [58][59][60]. [30][31][32]39,152,154] Arousal is facilitated by a1-and b-adrenoceptor stimulation in the medial basal forebrain [18].…”
Section: Methamphetamine Overdosementioning
confidence: 99%
“…Methamphetamine-induced mind-racing was correlated with activation in the anterior cingulated cortex and ventral striatum [157] Euphoria: high, elation, good drug effect, intoxication Inoue and colleagues proposed toxic plasma methamphetamine ranges of 200-5000 mg/l and fatal levels at >10 000 mg/l [56]. These figures should be considered as guides only, as fatalities have been reported at plasma concentrations as low as 90 mg/l [58], whereas survival has been reported at 9460 mg/l [37]. In terms of dose, fatal methamphetamine overdose has been reported following an intravenous dose of 20 mg [29] and elsewhere an experimental subject was observed to survive an intravenous dose of 640 mg methamphetamine, albeit with transient psychosis [40].…”
Section: Methamphetamine Overdosementioning
confidence: 99%
“…Studies suggest that the doses of METH used by humans recreationally or in medical studies range from 5 to 1000 mg over a 24 h period (Mitler et al, 1993;Simon et al, 2002). Post-mortem drug testing in a forensic study revealed a large range in the blood METH concentration among decedents (Logan et al, 1998). In this study low post-mortem METH concentrations were frequently observed, with the highest concentrations occurring in only a small subset of the decedents where METH was determined to be the direct cause of death, suggesting that lower doses are commonly used.…”
Section: Introductionmentioning
confidence: 99%